A method for improving test rig performance using passive components. (February 2015) - Johansson, Anders T.; Abrahamsson, Thomas J.S.
Abstract: The time waveform replication (TWR) algorithm is presently used in industry for calculating the actuation force needed to replicate a certain reference sensor output in a test rig. Power and force rate limitations restrict the feasible range of that actuation force. If the input force distribution of the reference test cannot be replicated in the test rig, the required test rig input force magnitudes may be large or the replication properties poor due to lack of controllability. To circumvent this, a theory of passive components to improve replication and limit the input force demands of dynamic test rigs is developed. The theory fits within the framework of the TWR algorithm. Abstract : Highlights: Theoretical and numerical verification of tracking problems due to lack of controllability. Development of a method to design passive control components to improve tracking. Numerical validation of improved tracking by proposed method.